1818 Miss. Laws 220 - (:unkn) unknown (My University, 1818)
Supplemental to an Act to erect the town of Netchez into a city, and to incorporate the same, § 2: That said president and select men, shall and may, from time to time, pass ordinances to regulate the keeping, carting and transporting gun powder or other combustible or dangerous materials[.]
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION